Hubungan Antara Gaya Hidup, Citra Merek Dan Persepsi Harga Terhadap Kepuasan Pelanggan Pada Pengguna Produk Fashion Brand Jims Honey (Studi Pada Mahasiswa Universitas Islam Malang 2021 ) - Isnaini, Eka Hikmatul Fajar; Salim, Muhammad Agus; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to examine the relationship between lifestyle, brand image, and price perception on cutomer satisfaction of Jims Honey fashion product users, with a focus on student of islamic University of malang Class of 2021. The method used is quantitative with a survey approach, distributing questionnaires to 97 respondents who have bought or used Jims Honey product. Data analysis was performed using multiple linear regression with spss 22 to identify the effect of independent variables on cutomer satisfaction. The result showed that lifestyle has a significant negative effect on customer satisfaction, with a beta coefficient of -0.247 and a sig value of 0,003, which means that the higher the lifestyle has a significant negative effect on customer satisfaction . Meanwhile, brand image and price perceptio have a significant positive effect on customer satisfaction. Price perception is proven to be the dominant factor affecting customer satisfaction, with a beta coefficient of 0,555. Keywords: Lifestyle, Brand Image, Price Perception, Customer Satisfaction, Jims Honey